Localization of magma injections, hydrothermal alteration, and deformation in a volcanic detachment (Piton des Neiges, La Réunion). (November 2016) - Famin, Vincent; Berthod, Carole; Michon, Laurent; Eychenne, Julia; Brothelande, Elodie; Mahabot, Marie-Myriam; Chaput, Marie
Highlights: Multiple sills were injected in a discontinuity within a basaltic volcano. The heat of cooling sills induced hydrothermal alteration and ductile deformation. Deformation occurred at ≤250 °C and at increasing fluid pressure. Volcano spreading did not occur by creep of a magmatic or hydrothermal system. Abstract: This contribution aims at understanding how magmatism, hydrothermal alteration, and deformation may have interacted to localize a detachment (a low-angle normal fault) in a basaltic volcano. Piton des Neiges, an inactive volcano of La Réunion Island, has been deeply cut by erosion, allowing its inner structure to be investigated. The deepest unit observed in the edifice is a kilometer-scale plutonic complex, the top of which is intruded by multiple sills. This zone of repeated sill intrusions has been interpreted as a detachment because it displays evidence of hydrothermal alteration in the greenschist facies linked to a brittle-ductile shear deformation. Deformation begins with cataclasis and is followed by mylonitization and chlorite crystallization, then by hydrofracturing and pumpellyite crystallization. Subsequent and post-deformation calcite crystallization occurs in voids such as fractures and vacuoles. Aluminium substitutions in chlorite suggest that the syn-deformation hydrothermal alteration did not exceed 250 °C and peaked in the deformation zone. Comparison of bulk-rock major element analyses of fresh, altered and deformed rocks shows that the zone of sill intrusion and deformation localized increased concentrations of P and K otherwise depleted in the footwall and hangingwall rocks, suggesting that the detachment acted as a trap for fluids. In contradiction with proposed models of volcano spreading, it is apparent that the portion of Piton des Neiges accessible to observation did not deform by creep of a large hydrothermal system or a plutonic complex below its solidus. Instead, the interface between the already cooled plutonic complex and the host rock acted as a brittle failure zone and was repeatedly intruded by magma injections. This localized heat source promoted hydrothermal alteration and low temperature creep in and around the discontinuity. The same process of magmatism-related weakening might occur on active volcanoes; it may, for instance, explain the slow post-eruptive deformation of the eastern flank of Piton de La Fournaise (the active volcano of La Réunion) observed since the April 2007 eruption.